2019
DOI: 10.1085/jgp.201812291
|View full text |Cite
|
Sign up to set email alerts
|

Bile acids inhibit human purinergic receptor P2X4 in a heterologous expression system

Abstract: The human purinergic receptor P2X4 is an ATP-gated nonselective cation channel expressed in a variety of cells, including hepatocytes and cholangiocytes. Ilyaskin et al. find that the bile acids inhibit P2X4 by stabilizing the channel's closed state, likely by interacting with its transmembrane domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…The released ATP is thought to inhibit ENaC in principal cells in an autocrine/paracrine manner via P2Y 2 -dependent purinergic signaling causing a rise in intracellular Ca 2+ . However, endogenous expression of purinergic receptors, and hence the responsiveness to extracellular ATP, is negligible in X. laevis oocytes ( 76 , 77 ). Moreover, it has been reported that application of ATP does not inhibit ENaC-mediated currents in the oocyte expression system ( 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…The released ATP is thought to inhibit ENaC in principal cells in an autocrine/paracrine manner via P2Y 2 -dependent purinergic signaling causing a rise in intracellular Ca 2+ . However, endogenous expression of purinergic receptors, and hence the responsiveness to extracellular ATP, is negligible in X. laevis oocytes ( 76 , 77 ). Moreover, it has been reported that application of ATP does not inhibit ENaC-mediated currents in the oocyte expression system ( 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PIPs bind to positively charged amino acids in the cytosolic C-terminal domain and inhibit P2X receptormediated currents. The P2X4 receptors, and to some extent the P2X2 receptors, are inhibited by high ethanol concentrations ($100 mM) (Ilyaskin, Sure, Nesterov, Haerteis, & Korbmacher, 2019;Müller, 2015;Sivcev et al, 2019). F I G U R E 1 Selected P2X receptor agonists, nucleotide-derived antagonists, and positive allosteric modulators…”
Section: P2x Receptor Agonistsmentioning
confidence: 99%
“…Finally, channels of the ENaC/DEG family share a surprising similarity in structure with purinoreceptor P2X channels: trimeric channels with two transmembrane segments and a large extracellular domain [83]. P2X channels have been excluded from this review as they do not belong to the ENaC/DEG family, nevertheless exploring proteins with similar structure and similar function can lead to new perspectives.…”
Section: Perspectivesmentioning
confidence: 99%